2013
DOI: 10.4236/ijohns.2013.24027
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Neck Mass as Sole Presenting Symptom for Seminoma in an Elderly Male

Abstract: We report an unusual case of genitourinary malignancy in an otherwise asymptomatic elderly male, which was discovered via workup of a supraclavicular neck mass. We present his clinical workup as well as the pathological workup and how it influenced our decision-making. A review of the literature is also discussed and demonstrates how uncommon it is for seminomas to present in this manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Wood et al demonstrated that cervical metastasis is almost exclusively left-sided, with 21 of 23 patients showing disease in supraclavicular or scalene lymph nodes [ 28 ]. Metastatic tumors can also appear in locations outside of the direct line of spread from the primary site [ 29 ]. A review by Vledder reported that 4 % of seminoma patients showed cervical metastasis and that only 5 % of these patients had the neck mass as their initial disease sign [ 30 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Wood et al demonstrated that cervical metastasis is almost exclusively left-sided, with 21 of 23 patients showing disease in supraclavicular or scalene lymph nodes [ 28 ]. Metastatic tumors can also appear in locations outside of the direct line of spread from the primary site [ 29 ]. A review by Vledder reported that 4 % of seminoma patients showed cervical metastasis and that only 5 % of these patients had the neck mass as their initial disease sign [ 30 ].…”
Section: Case Presentationmentioning
confidence: 99%